Expenditure and Employment Data for the Criminal Justice System (United States): CJEE Extracts File, 1995 ([Verlag nicht ermittelbar], 2001)
This file provides data on federal, state, and local governmental expenditures and employment for criminal justice activities in the United States. Information is supplied on police protection, judicial and legal services, and correctional institutions and agencies. Variables describing each of these criminal justice functions include number of and payroll for full-time, part-time, and full-time equivalent employees, current total and general expenditures, capital outlay, and intergovernmental expenditures.